2023
DOI: 10.1002/ece3.10296
|View full text |Cite
|
Sign up to set email alerts
|

Specialization patterns in symbiotic associations: A community perspective over spatial scales

Abstract: Specialization, contextualized in a resource axis of an organism niche, is a core concept in ecology. In biotic interactions, specialization can be determined by the range of interacting partners. Evolutionary and ecological factors, in combination with the surveyed scale (spatial, temporal, biological, and/or taxonomic), influence the conception of specialization. This study aimed to assess the specialization patterns and drivers in the lichen symbiosis, considering the interaction between the principal fungu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 159 publications
0
7
0
Order By: Relevance
“…When comparing specialization between bi-membered (cyanolichens and chlorolichens) and tri-membered (cephalolichens) lichen species, several patterns have been found. A high specialization hypothesized for cephalolichens [ 28 ] differed from the results of [ 20 ], showing that cephalolichens are more generalized than cyanolichens, and from other studies, which found no differences between both [ 25 , 29 ]. At the intrathalline (individual) level, and concerning cephalolichens specifically, it has been shown that most tripartite lichens contain the same Nostoc strain in all cephalodia of individual thalli [ 28 ], with the exception of Peltigera venosa , Lobaria pulmonaria , and three species of Pannaria ( P. farinosa , P. sphinctrina , and P. lobulifera ), which housed different cyanobionts in different cephalodia [ 23 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…When comparing specialization between bi-membered (cyanolichens and chlorolichens) and tri-membered (cephalolichens) lichen species, several patterns have been found. A high specialization hypothesized for cephalolichens [ 28 ] differed from the results of [ 20 ], showing that cephalolichens are more generalized than cyanolichens, and from other studies, which found no differences between both [ 25 , 29 ]. At the intrathalline (individual) level, and concerning cephalolichens specifically, it has been shown that most tripartite lichens contain the same Nostoc strain in all cephalodia of individual thalli [ 28 ], with the exception of Peltigera venosa , Lobaria pulmonaria , and three species of Pannaria ( P. farinosa , P. sphinctrina , and P. lobulifera ), which housed different cyanobionts in different cephalodia [ 23 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 70%
“…Two forests from a previous study carried out in Chile and sampled between 2017 and 2018 were used (Parque Nacional Torres del Paine and Isla Navarino) [ 20 ]. Forest stands were mostly formed by Notofagus pumilio with over 65% of cover.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because previous studies have shown that lichen-forming fungi tend to preferentially select photobiont lineages which are better adapted to local environmental conditions [ 18 , 19 , 20 , 21 , 22 , 23 ], we will here test the following hypotheses: (i) mycobionts in the R. farinacea group associate differentially with phycobionts in Macaronesia and Mediterranean, temperate, and Boreal regions in Europe; and (ii) the association with different phycobionts shapes the ecological distribution of the mycobionts. In doing this, we will investigate the complexity of interactions among mycobiont and phycobiont lineages, the degree of specificity across their geographic distributions [ 24 , 25 , 26 ], and the climatic niche width of the primary phycobionts.…”
Section: Introductionmentioning
confidence: 99%